Просто подставляешь -2 во все х, так и находится у
у = f(x)
y = 2*4 -3*(-2)+2
y = 16
(18-23)*(-32+28)/(-10)=(-5,6)
1)18-32= (-14)
2)-32+28=(-4)
3)(-14)*(-4)=56
4)56/(-10)=(-5,6)
0,9*(-0,2)-0,6*(0,2)=
1)0,9*(-0,2)=(-0,18)
2)0,6*0,2=0,12
3)(-0,18)-0,12=(-0,3)
(2/9-5/6)*(0,36:0,02)
1)2/9=22,22
2)5/6=83,33
3)0,22-0,83=(-0,61)
4)0,36/0,02=18
5)(-0,61)*18=(-10,98)
32,8 делим на 100 и умножаем на 80 получается 32,8·(4/5)=26,24
Нарисуйте все все будет хорошо
B(n)=b1*q^(n-1) q^(m-k)=b(m)/b(k)
подставляем
q=14/7=2, проверяем q^2=28/7=2^2 b1=7
Запишем формулу b(n)=7*2^(n-1)
b(4)=7*2^3=56
S(4)=7*((2^4)-1)/(2-1)=105